PRAKTEK BPJS KESEHATAN DALAM PERSPEKTIF HUKUM EKONOMI SYARI’AH - Lutfi Lutfi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2016)
Indonesian Ulema Council (MUI) issued a religious advice (fatwa)that theÂ Social Security AdministratorÂ Board (BPJS) Healthcare is not appropriate with sharia law. Thatreligious advice (fatwa) was issued through decisionfrom taken conjunction (ijtimaâ€™) by religious advice (fatwa) commissions of Indonesian Ulema Council (MUI) at at-Tauhidiyah boarding school Cikura, Bojong, Tegal, Central Java, in the middle past of 2015.Indonesian Ulema Council (MUI) alleged thattheÂ Social Security AdministratorÂ Board (BPJS) Healthcarewhich started since the beginning of 2014 until today, in practice containing elements of gambling (maisir), deception (gharar), and usury (riba).Related to that problem, the author wanted to know the standing of problem of theÂ Social Security AdministratorÂ Board (BPJS) Healthcare in proportion in a case study at theÂ Social Security AdministratorÂ Board (BPJS) Healthcare in Jember regency, which dynamic and religious views. Therefore the aim of this study was to determine the practice of theÂ Social Security AdministratorÂ Board (BPJS) Healthcare in Jember regency and to determine whether the existing mechanism in these institution is in conformity with the legal provisions of sharia economy or not.This study is qualitative research. The data collection methods that used are observation, interviews and documentation.The data obtained and analyzed using descriptive method.The validity of the data using perseverance techniqueor constancy observation.Based on the research that has been done, the result of this study are: 1) Practice oftheÂ Social Security AdministratorÂ Board (BPJS) Healthcare in serving members was in accordance to the provision of the National Social Security System (SJSN) Act NumberÂ 40 in 2004 and Social Security AdministratorÂ Board (BPJS) Act Number 24 in 2011 and some related regulations, such as a Presidential Regulation (Perpres); 2). According to the law of sharia economic perspective in the practice of that institution, there are several matters that appropriate to thesharia provisions, such as the mechanisms of participation and healthcare insurance. While in the aspects of the payment and fund management are not appropriate to the sharia provisions. There are extant elementsof gambling (maisir), deception (gharar), and usury (riba) in theÂ Social Security AdministratorÂ Board (BPJS) Healthcare in Jember regency